2014 14th International Conference on Frontiers in Handwriting Recognition 2014
DOI: 10.1109/icfhr.2014.53
|View full text |Cite
|
Sign up to set email alerts
|

Off-Line Handwritten Bilingual Name Recognition for Student Identification in an Automated Assessment System

Abstract: The Student name Identification System (SIS) proposed here was investigated for English and Thai languages combined. The proposed system recognises each name by using an approach for whole word recognition. In the proposed system, the Gaussian Grid Feature (GGF), and Modified Direction Feature (MDF), together with a proposed hybrid feature extraction technique called Water Reservoir, Loop and Gaussian Grid Feature (WRLGGF) were investigated on full word contour images of each name sample; Artificial neural net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Hence it can be concluded that an appreciating verification accuracy is attended in the experiment, although there is a huge scope of development in the forgery experiments. : Comparison of verification rates attained between the proposed study and the techniques [4], [5], [6], and [12] found in the literature given the similar datasets nature.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…Hence it can be concluded that an appreciating verification accuracy is attended in the experiment, although there is a huge scope of development in the forgery experiments. : Comparison of verification rates attained between the proposed study and the techniques [4], [5], [6], and [12] found in the literature given the similar datasets nature.…”
Section: Resultsmentioning
confidence: 87%
“…The verification rates decreased fractionally, and therefore, the results were not included in the table. The closest work which can be used for comparison were the work proposed by [4], [5], [6], and [12]. The first three studies' results were obtained from SIS which used name components for identification process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations